Call of duty: an exploration of the factors influencing NHS professionals to report adult protection concerns. Issue 3 (13th June 2016) - Fennell, Kate
Abstract : Purpose: – The Adult Support and Protection (Scotland) Act 2007 places a duty on Councils to investigate the circumstances of adults who, because of a disability, health condition or illness are unable to safeguard themselves from harm. Public partner agencies, including the NHS have a statutory obligation to bring to the attention of the Council those individuals who may be at risk of harm. Health professionals cooperate with adult protection investigations and participate in the development of adult support and protection plans, yet do not appear to be initiating adult protection referrals with the Council. Low reporting by health has also been recognised as a national issue. The purpose of this paper is to explore what promotes and what prohibits the identification and reporting of situations of abuse within the Scottish Legislative Framework. Understanding the decision-making processes of prospective reporters would potentially allow the barriers to be reduced and the supports to be strengthened. Design/methodology/approach: – The research strategy is based on a literature review, a web-based survey and semi-structured interviews with health professionals within community learning and community mental health teams. Findings: – The findings point to a number of inter-related factors which impinge upon the professional's confidence to initiate adult protection referrals. Workers must first recognise harm as conduct which needs to be reported and addressed. They need to be familiar with referral procedures and be assured that their concerns will be dealt with appropriately. Health professionals are more likely to report if they are based in an environment which supports honest and open discussion regarding harm, without over-concern about agency reputation or resources. Access to multi-disciplinary consultation and support, particularly in relation to more ambiguous protection situations, was viewed as fundamental to reporting. Originality/value: – This small scale study adds to a developing bank of literature providing a Scottish perspective on protecting adults. It offers some insight into reporting decisions from the viewpoint of community health professionals.